Respuesta :

Answer:

[tex]6, \frac{2}{3},\frac{1}{2}[/tex]

Step-by-step explanation:

Since 6 is a zero f f(x), then (x-6) is a factor of f(x). Now we will find the others factors

First, we divide f(x) by x-6:

1. divide the highest degree coefficients of the denominator [tex]6x^3-29x^2-40x-12[/tex] and divisor [tex]x-6[/tex]:

quotient: [tex]\frac{6x^3}{x}=6x^2[/tex]

2. Multiply [tex]x-6[/tex] by [tex]6x ^ 2[/tex]:[tex]6x^3-36x^2[/tex].

Subtract [tex]6x^3-36x^2[/tex] from [tex]6x^3-29x^2-40x-12[/tex] to obtain a new remainder: [tex]7x^2-40x-12[/tex]

Now, divide the new remainder by [tex]x-6[/tex]. We repeat the previous steps:

3. quotient: [tex]\frac{7x^2}{x}=7x[/tex]

4. Multiply [tex]x-6[/tex] by [tex]7x[/tex]:[tex]7x^2+42x[/tex]

Subtract [tex]7x^2+42x[/tex] from [tex]7x^2-40x-12[/tex] to obtain a new remainder: [tex]2x-12[/tex].

5. Divide [tex]2x-12[/tex] by [tex]x-6[/tex]. We obtain [tex]\frac{2x-12}{x-6}=2[/tex] and the new remainder is 0.

So, the quotiente [tex]\frac{6x^3-29x^2-40x-12}{x-6}=6x^2+7x+2[/tex]

Then, [tex]6x^3-29x^2-40x-12=(x-6)(6x^2+7x+2)[/tex]

For find the other two zeros of f(x) we have the zeros of [tex]6x^2+7x+2[/tex].

We use the formula: [tex]x_{1,2}=\frac{-b\pm\sqrt{b^2-4ac}}{2a}[/tex],

Then, [tex]x_{1,2}=\frac{7\pm\sqrt{7^2-4*6*2}}{2*6}=\frac{7\pm 1}{12}\\x_1=\frac{8}{12}=\frac{2}{3}\\x_2=\frac{6}{12}=\frac{1}{2}[/tex]

Then the zeros of f(x) are: [tex]6, \frac{2}{3},\frac{1}{2}[/tex]